Modulating the intralayer and interlayer valley excitons in WS2 through interaction with AlGaN - Zeng, Xinlong; Kang, Wenyu; Zhou, Xiaowen; Li, Linglong; Xia, Yuanzheng; Liu, Haiyang; Yang, Chengbiao; Wu, Yaping; Wu, Zhiming; Li, Xu; Kang, Junyong (Science China materials, 2023)
The fine-tuning of exciton transition and valley polarization process in two-dimensional materials have drawn tremendous research interest due to their rich valley-contrasting physics. Here, we demonstrate highly tunable exciton and valley characteristics in monolayer and bilayer WS 2 through coupling to AlGaN with different doping levels. A notable redshift in exciton energy is observed by interfacing WS 2 with n-type AlGaN. More interestingly, an interlayer exciton peak emerges as a result of the formation of type-II band alignment in bilayer WS2. Both the interlayer and intralayer exciton energies are tunable by the twist angle of bilayer WS 2 . A high valley polarization of 82.2% is achieved in monolayer WS 2 at 13 K by coupling with n-type AlGaN, due to the faster exciton decay rate through electron-phonon interaction and the reduced intervalley scattering by doping-induced carrier screening. The valley polarization of interlayer exciton is higher than that of the intralayer exciton, due to the suppressed intervalley scattering resulting from the reduced electron-hole interaction. This work has presented a facile and efficient technique to modulate the excitonic properties of 2D materials. The reported high valley polarization in monolayer WS 2 and the discovery of interlayer exciton in bilayer WS 2 will trigger innovative study in valley exciton physics and facilitate emerging valleytronic applications.